Restoring the regenerative balance in neuromuscular disorders: satellite cell activation as therapeutic target in Pompe disease - Schaaf, Gerben J. (Ann Transl Med, 2019)
Skeletal muscle is capable of efficiently regenerating after damage in a process mediated by tissue-resident stem cells called satellite cells. This regenerative potential is often compromised under muscle-degenerative conditions. Consequently, the damage produced during degeneration is not efficiently repaired and the balance between repair and damage is lost. Here we review recent progress on the role of satellite cell-mediated repair in neuromuscular disorders with a focus on Pompe disease, an inherited metabolic myopathy caused by deficiency of the lysosomal enzyme acid alpha glucosidase (GAA). Studies performed in patient biopsies as well as in Pompe disease mouse models demonstrate that muscle regeneration activity is compromised despite progressing muscle damage. We describe disease-specific mechanisms of satellite cell dysfunction to highlight the differences between Pompe disease and muscle dystrophies. The mechanisms involved provide possible targets for therapy, such as modulation of autophagy, muscle exercise, and pharmacological modulation of satellite cell activation. Most of these approaches are still experimental, although promising in animal models, still warrant caution with respect to their safety and efficiency profile.